Dynamics of Career Choice in High School: The Role of Personal Interests and Family Socio-Economic Status - Lika Widiawati; Firman; Netrawati; Mohd Nazri Abdul Rahman (Journal Of Psychology, Counseling And Education, 2024)
The career selection process is one of the most crucial decisions in a person's life. This decision shapes the direction their life will take. Career selection is also an inevitable part of the social aspect that influences individuals after passing through certain developmental stages. This research delves into the factors influencing high school students in choosing their careers. Based on Donal Super's theory, there are internal factors (such as interests and talents) and external factors (such as family influence and socioeconomic status) that impact an individual's career choice. Through a literature-based approach and data analysis from various sources, this study underscores the complexity of the interaction among these factors in students' career decisions. With a profound understanding, educational institutions and parents can provide appropriate guidance, help students recognize their interests and talents, and consider environmental influences, thereby opening avenues for career development aligned with students' potential.